Development Of Sustainable Employees' Well-Being Model in the Malaysian Palm Oil Industry (S/O 14841) - E-Vahdati, Sahar; Mohd Nor, Nor Azila; Ahmad Zaluki, Nurwati Ashikkin; Abd Rahim, Nazahah (UUM, 2023)
The Malaysian Palm Oil Board noted that the palm oil industry is a major contributor to the GDP of the agriculture sector in 2018 at 37.9% which have enjoyed tremendous growth recently. However, well-being which is defined as employees' perceptions about their work and working environment dropped in comparison with previous years. Minimum wage policy in Malaysia heightens the issues of labour rights among local and foreign workers as well as issues related to job satisfaction and health. The objective of this study is to develop a model of employee wellbeing in the Malaysian palm oil industry through Triple Bottom line (TBL) approaches based on the Social Exchange Theory (SET) as a backbone and investigating the factors motivating and de-motivating employees. Data was collected using quantitative and qualitative approaches through surveys, interviews with employees and government bodies. This research contributes to the extension of Triple Bottom Line Model development of employees' well-being and serves as a guideline for stakeholders in the industry namely Consumer goods manufacturers, policymakers, plantation companies, Ministry of Primary Industries, Ministries of Agriculture, and The Malaysian Palm Oil Board.